MEWUJUDKAN PUSTAKAWAN KEMENTERIAN KESEHATAN YANG KOMPETEN DAN PROFESIONAL MELALUI PEMILIHAN PUSTAKAWAN INOVATIF TERBAIK - RESTY KIANTINI (CENDEKIA: Jurnal Ilmu Pengetahuan, 2022)
The Ministry of Health Library is a builder library for libraries and librarians within the Ministry of Health spread throughout Indonesia. The success of the library is largely determined by the role of the librarian. Because the librarian is a profession that has a major contribution in realizing the noble ideals of the Indonesian nation in the intellectual life of the nation. Based on this, the Ministry of Health Library held a Selection of the Best Innovative Librarian. The method used in writing this scientific paper is best practice. Best Practice is an idea or new steps that make an outstanding, sustainable and innovative contribution in improving the process development and quality of education. Best Practice needs to be disseminated to others with various strategies in various places repeatedly so that it can be imitated and adopted by others. The selection of the Best Innovative Librarian was carried out in several stages. Starting from making the TOR for activities, entering activity items into the RKAKL, determining the theme of the activity, making guidelines, compiling a Committee Decree. The Best Innovative Librarian Assessment is done by looking at the completeness of documents, innovation papers and presentations. The one who gets the best score from the jury will be designated as the Best Innovative Librarian within the Ministry of Health. The Best Innovative Librarian 1 to 3 and expectations 1 to 3. The Best Innovative Librarian received awards and prizes at the Publication and Public Service Award Night of the Ministry of Health which was attended by the Minister of Health, Menpan-RB and the Head of the National Library. Librarians are the main key to the sustainability and success of a library. The selection of the Best Innovative Librarian was held as a form of appreciation and appreciation for librarians within the Ministry of Health. It is hoped that this activity can motivate librarians in the Ministry of Health to continue to work, innovate, perform and excel and have competitiveness with other professions. ABSTRAKPerpustakaan Kementerian Kesehatan merupakan perpustakaan pembina bagi perpustakaan dan pustakawan di lingkungan Kementerian Kesehatan yang tersebar di seluruh Indonesia. Keberhasilan perpustakaan sangat ditentukan oleh peran Pustakawan. Karena pustakawan merupakan profesi yang memiliki kontribusi besar dalam mewujudkan cita-cita luhur bangsa Indonesia dalam mencerdaskan kehidupan bangsa. Berdasarkan hal tersebut Perpustakaaan Kementerian Kesehatan menyelenggarakan Pemilihan Pustakawan Inovatif Terbaik. Metode yang digunakan dalam penulisan karya ilmiah ini adalah best practise. Best Practice adalah suatu ide atau langkah-langkah baru yang memberikan kontribusi luar biasa, berkesinambungan dan inovatif dalam memperbaiki pengembangan proses dan kualitas pendidikan. Best Practice perlu didiseminasikan kepada orang lain dengan berbagai strategi diberbagai tempat secara berulang-ulang sehingga dapat dicontoh dan diadopsi oleh orang lain. Pemilihan Pustakawan Inovatif Terbaik dilaksanakan melalui beberapa tahap. Diawali dari pembuatan TOR kegiatan, memasukkan butir kegiatan kedalam RKAKL, menentukan tema kegiatan, membuat pedoman, menyusun SK Kepanitiaan. Penilaian Pustakawan Inovatif Terbaik dilakukan dengan cara melihat kelengkapan dokumen, makalah inovasi dan presentasi. Yang mendapat nilai terbaik dari dewan juri akan ditetapkan sebagai Pustakawan Inovatif Terbaik di lingkungan Kementerian Kesehatan. Terpilih Pustakawan Inovatif Terbaik 1 sd 3 dan harapan 1 s/d 3. Pustakawan Inovatif Terbaik mendapatkan penghargaan dan hadiah di Malam Penghargaan Publikasi dan Pelayanan Publik Kementerian Kesehatan yang dihadiri oleh Menkes, Menpan-RB dan Kepala Perpusnas. Pustakawan menjadi kunci utama keberlangsungan dan keberhasilan sebuah perpustakaan. Pemilihan Pustakawan Inovatif Terbaik dilaksanakan sebagai suatu bentuk apresiasi dan penghargaan kepada pustakawan di lingkungan Kementerian Kesehatan. Diharapkan dengan adanya kegiatan ini dapat memotivasi pustakawan di lingkungan Kementerian Kesehatan untuk terus berkarya, berinovasi, berkinerja dan berprestasi serta memiliki daya saing dengan profesi lainnya.